English for Digital Workforce: Pelatihan Keterampilan Bahasa Inggris Siswa dalam Dunia Kerja Digital - Sitti Suharni; Prisma Yunia Putri; Khairunnisa Noviantari; Rika Ilma Putri; Made Dewi Purnami (Yayasan Literasi Sains Indonesia, 2025)
This English language training program was designed in response to the increasing demand for global workforce readiness in the digital era, where English proficiency is a key skill for professional communication. The training was conducted offline on May 16, 2025, at SMK Negeri 4 Bandar Lampung, involving six mentoring lecturers and 35 student participants. The main objective of the activity was to equip students with basic knowledge of the importance of English in the digital work environment and to introduce strategies for developing English skills for professional purposes. The training employed interactive lectures, group discussions, and Q&A sessions. The program was divided into three main sessions: (1) an introduction to the digital job market and the urgency of English language mastery, (2) strategies for learning English for workplace needs, and (3) an overview of overseas work and study opportunities. Based on the preliminary survey, most students had limited understanding of the significance of English proficiency in a global context. However, post-training evaluations revealed a significant improvement in students’ knowledge, enthusiasm, and active participation, especially during discussion sessions. The program is expected to serve as an initial step in raising awareness and preparing young generations to face global challenges with confidence, adaptability, and linguistic competence. Furthermore, this training provides a foundation for future, more intensive programs aimed at enhancing vocational students’ readiness for the digital job market.